Conservative management of cervical intraepithelial neoplasia grade 2 and immunohistochemical staining of p16 and Ki-67: Data from a Brazilian institution - Amanda Leal Ferreira; Yara Lúcia Mendes Furtado de Melo; Elyzabeth Avvad Portari; Dione Corrêa Araújo Dock; Nilma Valéria Ferreira Caldeira; Saint Clair dos Santos Gomes Júnior; Fabio Bastos Russomano; Cecília Vianna de Andrade (PLoS ONE, 2026)
Introduction Cervical intraepithelial neoplasia grade 2 (CIN2) includes both transient HPV infections and precursor lesions of cervical cancer. Conservative management aims to avoid overtreatment, especially in reproductive-aged women. Objective To describe the clinical outcomes and time to lesion regression among conservatively managed, biopsy-confirmed CIN2 cases, and to explore whether baseline characteristics, including p16 and Ki-67, were associated with lesion regression. Materials and methods An observational cohort study was conducted in patients with CIN2, as determined by cervical biopsy. Participants were followed up with cytology and colposcopy every 6 months, and outcomes were categorized as regression or no regression. At least two pathologists evaluated p16 immunohistochemical staining according to LAST criteria. Ki-67 staining was considered positive when at least 50% of cells in the lesion were stained, as determined by digital quantification. Bivariate analysis and survival curve analyses were conducted, with significant associations defined as p-values <0.05. Results Fifty patients with a mean age of 30.5 years were included in the study; 76% (38/50) showed regression. The median time to regression was 357 days (SE = 61.4 days; 95% CI: 236.6–477.4 days). The baseline characteristics, including p16 and Ki-67, were not statistically associated with regression, likely due to the small sample size. Conclusion CIN2 regression occurred in 76% of cases, with median times of approximately 12 months for regression and 32 months for progression. No statistically significant associations were detected between baseline characteristics, including biomarkers, and lesion regression in this exploratory study.